Miről álmodik a lelkipásztor? Telegdi T. István alpestesi lelkész álomfeljegyzései - Sándor-Előd ŐSZ (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica, 2017)
What Does a Reformed Pastor Dream of? The Notes of István T. Telegdi, Reformed Pastor of Alpestes about His Dreams.